Identification of A Cold-active Lipase Producing Strain, Optimization of Fermentation Conditions and Analysis of Enzymatic Properties - Siyuan LIU; Dongchen SHEN; Zheng LIU; Liying LU; Heng XU; Airong DONG (Shipin gongye ke-ji, 2023)
To screen strains with high production of cold-active lipase and optimize enzyme production conditions, as well as to provide production information for the industrial development of lipase, a cold-active lipase producing strain was screened from soil samples in Mohe County, Heilongjiang Province, and identified as Serratia plymuthica by morphological identification, physiological and biochemical experiments and molecular biology. The effects of different factors such as temperature, pH, loading volume, inoculum, carbon source, nitrogen source, metal ion and inducer on the enzyme production of the strain were investigated by single-factor experiments, as well as the optimization of the addition of olive oil, peptone and loading volume by Plackett-Burman experiment, hill climbing test and response surface design. The results showed that the optimal enzyme production conditions were 20 ℃, pH7.5, loading volume 42 mL, inoculum 0.5%, 20 g/L maltose, 14 g/L peptone, 0.5 g/L MgSO4·7H2O and 46 mL/L olive oil. The lipase activity under this optimized condition was 98.05 U/mL, which was 5.85 times higher than that before optimization. The results of enzymatic properties showed that the optimum temperature of this lipase was 30 ℃, which was a low temperature lipase, and the optimum reaction pH was 7. Mg2+ could obviously promote the enzyme activity. The organic solvents methanol and ethanol obviously inhibited the enzyme activity, while n-hexane could obviously promote the enzyme activity. The conclusion can provide some theoretical basis and methodological guidance for the development and utilization of microbial resources and industrial production of low-temperature lipase.